Computerised cognitive assessment of athletes with sports related head injury. Issue 5 (1st October 2001) - Collie, A; Darby, D; Maruff, P
Abstract : Professional and amateur participants in many sports are at risk of brain injury caused by impact with other players or objects. In many cases, mild cognitive deficits may persist after the common neurological signs of brain injury have passed. In recent years, the athlete's cognitive status after concussion has been measured with conventional "paper and pencil" neuropsychological tests. However, such tests are not ideal for sporting settings, as they are designed for the detection of gross cognitive impairments at a single assessment, not for the identification of mild cognitive deficits on repeated assessment. A number of computerised cognitive assessment tests and test batteries have been developed over the past two decades. These batteries offer major scientific and practical advantages over conventional neuropsychological tests which make them ideal for the assessment of cognitive function in sportspeople. This review first describes the problems associated with cognitive assessment of people with sports related cognitive deficits, and then critically examines the utility of conventional neuropsychological and computerised cognitive tests in sporting settings.